Prevalence and Characteristics of Rheumatoid-Associated Autoantibodies in Patients with COVID-19 - Xu C; Fan J; Luo Y; Zhao Z; Tang P; Yang G; Pan Y; Guo S; Liu Y; Xiong Y; Xie W; Long X (Dove Medical Press, 2021)
Chen Xu,1,* Junli Fan,1,* Yi Luo,1,* Ziwu Zhao,1,* Peng Tang,1,* Gui Yang,1 Yunbao Pan,1 Shuang Guo,1 Yingjuan Liu,1 Yong Xiong,2 Wen Xie,1 Xinghua Long1 1Department of Laboratory Medicine, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China; 2Department of infectious diseases, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Xinghua Long; Wen XieDepartment of Laboratory Medicine, Zhongnan Hospital of Wuhan University, Wuhan, People's Republic of ChinaEmail zhoulongxinghua@qq.com; whxw007@126.comObjective: Patients with rheumatic immune diseases were more likely to develop severe or critical COVID-19. We aimed to determine whether rheumatoid factor antibodies were present in COVID patients and the level and type of rheumatoid factor antibodies produced in COVID-19 patients were related to the degree of the patient's condition. The study also aimed to determine the prevalence and characteristics of rheumatoid factor antibodies in patients with COVID-19.Methods: Sera collected from 129 patients with COVID-19 were tested for rheumatoid factor antibodies by ELISA. Five patients were tracked for several months to monitor dynamic changes of these antibodies.Results: Rheumatoid-associated autoantibodies were detected in 20.16% of patients (26/129) following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In addition, IgM-RF was primarily present in critically ill patients, while IgA-RF was mainly present in mild patients. Five patients were able to track for several months to monitor dynamic changes of these antibodies. Rheumatoid factor antibodies peaks in the later phase of the disease and last for longer time. Anti-Jo-1 antibody was found in one of the five patients.Conclusion: This was the case series report that rheumatoid-associated autoantibodies are present in patients with COVID-19. The clinical significance of these antibodies was not fully understood and needed further characterization. These autoantibodies are related to the severity of the patient's disease and exist for a long time in the patient's body, while their impact on the patient's health is unknown.Keywords: rheumatoid factor, IgA-RF, IgG-RF, IgM-RF, anti-Jo-1, COVID-19, SARS-CoV-2